2013
DOI: 10.7482/0003-9438-56-091
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vivo effect</i> of <i>Berberis lyceum</i> and <i>Silybum marianum</i> on production performance and immune status of broiler chickens

Abstract: Abstract. We conducted an in vivo experiment to study the effect of water-based infusion of Berberis lyceum and Silybum marianum on production performance and immune level of broiler chicks. A total of 120 day old broiler chicks was obtained from the same parent flock, and divided into four experimental groups i.e., WBI-0 (control), WBI-5 (5 ml/l), WBI-10 (10 ml/l) and WBI-20 (20 ml/l). Each group was further divided into three replicates with 10 chicks per replicate in a completely randomized design. The bird… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Several feed additives have been proposed such as probiotic (Khan and Naz 2013;Khan et al2013aKhan et al , b, 2014aAlam et al 2020;Shah et al 2020), prebiotics (Chand et al2016(Chand et al , 2019Tufail et al 2019;Haq et al 2020), enzymes (Abd El-Hack et al 2018;Sultan et al 2019;Alam et al 2020;Jabbar et al 2021a, b), and herbs (Khan et al 2012a, b, c, d;Mushtaq et al 2013;Dhama et al 2014;Alzawqari et al 2016;Hafeez et al 2020a, b, c;Ahmad et al 2020;Chand et al 2021;Israr et al 2021;Khan et al 2021a, b;Shuaib et al 2021a, b), which have been reported in poultry (Fig. 1) and illustrated by Gadde et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several feed additives have been proposed such as probiotic (Khan and Naz 2013;Khan et al2013aKhan et al , b, 2014aAlam et al 2020;Shah et al 2020), prebiotics (Chand et al2016(Chand et al , 2019Tufail et al 2019;Haq et al 2020), enzymes (Abd El-Hack et al 2018;Sultan et al 2019;Alam et al 2020;Jabbar et al 2021a, b), and herbs (Khan et al 2012a, b, c, d;Mushtaq et al 2013;Dhama et al 2014;Alzawqari et al 2016;Hafeez et al 2020a, b, c;Ahmad et al 2020;Chand et al 2021;Israr et al 2021;Khan et al 2021a, b;Shuaib et al 2021a, b), which have been reported in poultry (Fig. 1) and illustrated by Gadde et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Examination of humoral immunity parameters of Ross 308 strain broiler chickens fed a diet supplemented with different levels of raw and heated SM seeds indicated that SRBC concentrations increased with SM supplementation compared with the control (Mozaffarpour Toubkanlou et al, 2017). Amiri Dumari et al ( 2014) reported that feeding SM (0.5 and 1%) had no effect on antibody titers of Newcastle and influenza, but Mushtaq et al (2013) reported that supplementation of SM extract and barberry in broiler diets increased antibody quantity against Newcastle and bronchitis.…”
Section: Immune Systemmentioning
confidence: 99%
“…7 Major alkaloid of the plant is berberine, which is known for its activity against cholera and acute diarrhea. 8 Previous studies shows that Berberis lycium plant has a wide range of biological activities including anti-hyperglycemic, 9,10 antihyperlipidemic, 11,12 anti-cancer and anti-tumor, 13,14 wound healing, 15 bone healing, 16 antimicrobial, 17,18 anticoccidial, 19 anti-oxidant, 20,21 immunity enhancing, hepatoprotective, 22,23 anti-urolithic and anthelmintic. 24 As mentioned in the earlier reported literature B. lycium is found to be an important herb which shows numerous biological activities and used widely as folk medicine in India.…”
Section: Introductionmentioning
confidence: 99%